Derivative of oxygafluorene and di-tert-butyl carbazole as the host with very high hole mobility for high-efficiency blue phosphorescent organic light-emitting diodes. (July 2016) - Gudeika, Dalius; Volyniuk, Dmytro; Grazulevicius, Juozas V.; Skuodis, Eigirdas; Yu, Sian-Yin; Liou, Wei-Tong; Chen, Li-Yin; Shiu, Yi-Jiun
Abstract: Derivative of oxygafluorene and di- tert -butyl carbazole was synthesized as the host material for high-efficiency blue phosphorescent organic light-emitting diodes. It exhibited moderate thermal stability with 5% weight loss temperature of 337 °C and glass-forming ability with the glass-transition temperature of 65 °C. The solid-state ionization potential of di- tert -butyl carbazolyl-substituted oxygafluorene was found to be 5.54 eV as established by electron photoemission spectrometry. It showed low-dispersity hole transport with time-of-flight hole mobilities of 10 −2  cm 2  V −1  s −1 observed at high electric fields. Blue devices based on the synthesized compound showed high external quantum efficiency up to 16.5% and low efficiency roll-off. Highlights: Derivative of oxygafluorene and di- tert -butyl carbazole was synthesized. The solid sample showed triplet energy of 2.81 eV. The hole mobility reached 10 −2  cm 2 V −1 s −1  at high electric fields. Blue devices showed external quantum efficiency of 16.5%.